Entendendo a vulnerabilidade do consumidor cego: traços de personalidade e adaptação ao mercado de consumo - Falchetti, Claudia (2015)
The purpose of this paper was to examine the vulnerability perceived by visually impaired consumers. By analysing the narratives of sixteen people that have acquired visual impairment, was developed an understanding of the internal and external factors that affect their degree of vulnerability and identified their coping strategies. Data analysis consisted of latent content analysis, which focus on content interpretation and on a search for the meaning of the particular experiences, events, and states reported by the respondents. These were divided into three profiles that differ with respect to how internal and external resources are inter-related in the face of consumer vulnerability. Results show how emotional wellbeing, consumption-facilitating social support, acceptance, autonomy and perceptions about marketplace difficulties relate to coping mechanisms. This study makes a contribution to consumer vulnerability literature both by furthering the research on the vulnerability perceived by visually impaired consumers and by identifying the mitigating or aggravating factors related to those individuals, along with their coping strategies. Results are reported that may lead to the development of both other research projects that aim to understand these people and programmes that lead to improved quality of life and wellbeing for these particular consumers.